The self determined motivation fall in school kids - Cecchini Estrada, José A.; Fernández Losa, Jorge Luis; González González de Mesa, Carmen; Fernández Río, Javier; Méndez Giménez, Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2012)
The purpose of this study is to analyze the progressive decommitment of young kids towards physical activity from the Self Determination Theory perspective(Deci & Ryan, 1985, 1991). The sample was formed by 705 students, ages 10 through 14 (329 were elementary students, and 376 were junior high students, with an average age of 12.7). Three MANOVA analysis were conducted 2 (gender) X 2 (educative cycles), that showed that the elementary education students showed a more adaptive than secondary education. The Self Determination Theory predicts that these results are the consequence of social factors. Therefor this investigation points out key factors that should be taken into account in the physical education class such as collaborative learning, a classroom environment directed towards self-improvement, and student participation to make decisions in the classroom.